Investigation of Mechanical, Thermal and Morphological Properties of Biaxial Glass Fiber/Waste Paper Reinforced Polyester Composites - (:unkn) unknown (WALTER DE GRUYTER GMBH, 2009)
The recovery and recycling of lignocellulosic fibers have experienced an important increase in the last few years. In 2004, the apparent world consumption of virgin cellulosic fibers for papermaking purposes was around 188 million tones. The apparent consumption of recovered paper in the world during the same year was 177 million tones. This value was only 6.2% lower than the apparent consumption of virgin fibers from these values. It can be observed that the availability of this raw material is really important and their importance will grow when the consumption per capita of paper in developing countries achieves comparable values of developed countries. Composite materials have been used in the industry for many years. Especially, textile reinforced composites are used in many applications because of their excellent mechanical properties. Marine, automotive and aerospace, packaging industries are the main consumers of textile reinforced composites. In this study, waste newspaper/polyester resin, waste newspaper/polyester resin/biaxial warp knitted fabric and waste Kraft paper/polyester resin, waste Kraft paper/polyester resin/biaxial warp knitted fabric composite structures were produced. The changes of characteristic of the composite structure were recorded by mechanical tests, (tensile strength, strain, elasticity modulus, and izod impact strength), X-ray diffraction spectra and their morphological characteristics by means of SEM.
Keywords: Newspaper; recycled newspaper; Kraft paper; biaxial warp knitted; composite